Pto Interaction Proteins: Critical Regulators in Plant Development and Stress Response - Sun, Meihong; Qiu, Liuliu; Liu, Yanshuang; Zhang, Heng; Zhang, Yongxue; Qin, Yi; Mao, Yingjie; Zhou, Min; Du, Xiaosha; Qin, Zhi; Dai, Shaojun (Frontiers in Plant Science, 2022)
Pto interaction (Pti) proteins are a group of proteins that can be phosphorylated by serine/threonine protein kinase Pto, which have diverse functions in plant development and stress response. Here we analyzed the phylogenetic relationship, gene structure and conserved motifs of Pti1s, and predicted the potential cis-elements in the promoters of Pti1 genes using bioinformatics methods. Importantly, we systematically summarized the diverse functions of Pti1s in tomato, rice, Arabidopsis, potato, apple, and cucumber. The potential cis-elements in promoters of Pti1s decide their function diversity in response to various biotic and abiotic stresses. The protein kinase Pti1 was phosphorylated by Pto and then modulate downstream signaling pathways for PTI and ETI in disease insistence process. In addition, some transcription factors have been defined as Ptis (Pti4, 5 and 6) originally, which actually were ethylene-response factors (ERFs). Pti4, 5 and 6 were modulated by salicylic acid (SA), jasmonate (JA), and ethylene signaling pathways and regulated diverse defense-related gene expression to cope with Pst infection and insect wounding.